What are your words? : a book about pronouns - Locke, Katherine (Little, Brown and Company, 2021)
Ari knows a lot of words for neighbors, including the pronouns each prefers, and with help from Uncle Lior, who always asks "What are your words," figures out which pronouns--and other words--fit best today.